Applying delay tolerant networking routing algorithms in maritime communications - Lambrinos, Lambros; Djouvas, Constantinos; Chrysostomou, Chrysostomos (My University, 2013)
The availability of off-the-shelf equipment that facilitates long range wireless connectivity can prove to be useful in maritime communications. By establishing terrestrial wireless links, vessels may exchange data between them or with shore-based stations avoiding the use of costly satellite connectivity. On the other hand, vessel mobility and large distances between its nodes make a wireless maritime network hard to manage; frequent disconnections are expected to be the norm in this primarily low node density environment. As such, maritime communications appear as an ideal environment for delay tolerant networking. To this extent, we use actual vessel mobility data to evaluate some existing delay tolerant networking routing algorithms and identify where they fall short from the perspective of our particular domain. It appears that a hybrid approach in the form of a new routing algorithm that addresses the particular characteristics of a maritime network can prove beneficial.
Keywords: Data routing algorithm; Delay tolerant network; Maritime communication network